THE INFLUENCE OF CAREER MOTIVATION, FINANCIAL REWARDS, AND PROFESSIONAL RECOGNITION ON ACCOUNTING GRADUATES’ INTEREST IN OBTAINING CERTIFIED PUBLIC ACCOUNTANT (CPA) CERTIFICATION - Cok Bagus Wedananda Satwika; Luh Gede Krisna Dewi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the influence of career motivation, financial rewards, and professional recognition on accounting graduates’ interest in obtaining Certified Public Accountant (CPA) certification. In the increasingly competitive accounting profession, professional certification has become essential for distinguishing oneself and advancing a career. Despite producing an average of 35,000 accounting graduates annually, Indonesia has a relatively low number of CPA certified accountants only about 2,064 as of August 31, 2023. This phenomenon indicates a lack of interest among graduates in taking the CPA certification exam. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 212 active master’s students in the accounting study program at Udayana University, selected using a proportionate stratified random sampling technique. The independent variables in this study are career motivation, financial rewards, and professional recognition, while the dependent variable is the interest of accounting graduates in obtaining CPA certification. Data analysis was conducted using multiple linear regression. The findings reveal that career motivation, financial rewards, and professional recognition each have a positive and significant effect on accounting graduates’ interest in obtaining CPA certification. These results align with the Theory of Planned Behavior (TPB), which explains that an individual’s intention to engage in a behavior is influenced by their attitude toward the behavior, subjective norms, and perceived behavioral control.